SINTESIS FEROMON 3-METIL 4-OKTANOL SEBAGAI ZAT PEMBASMI HAMA KUMBANG KELAPA Rhynchoporus spp. - Evy Setiawati; Khoerul Anwar (Kementerian Perindustrian, 2011)
The compound of 3-methyl-4-octanol had been synthesized by the formation of Grignard reagent sec-buthyl magnesium bromide. The choosing of reactant 2-bromo butane and n-pentanal were resulted from retrosynthesize analysize of 3-methyl-4octanol pheromone. The reaction of sec-buthyl magnesium bromide was done at temperature 400C for 30 minutes, while the reaction between this reagent with n-pentanal was done for two hours. The formed compound was hydrolized using saturated NH4Cl solution and then cooled. The compound was identified using Infra Red spectrophotometre (IR), Gas Chromatography (GC), and Gas Chromatography-Mass Spectroscopy (GC-MS). The yield persentage of the compound was 12,70%.Keywords: synthesis, hydrolisis, pheromone, Grignard reagent, Rhynchoporus spp